The Effect of Scapular Stabilization and McKenzie Neck Exercise on Craniovertebral Angle in Adolescents Aged 13–15 Years with Forward Head Posture at SMP Muhammadiyah 16 - Isidorus Jehaman; Desy Fitriani Tanjung; Waode Riska Astuti Aini; Raynald Ignasius Ginting (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Body posture can be impaired when daily activities are performed in non-ergonomic positions, resulting in uneven load distribution throughout the body. One of the most common postural disorders found in adolescents is a forward-leaning head position, known as forward head posture. This condition can be corrected through appropriate exercises, such as scapular stabilization exercises, which aim to improve scapular positioning and enhance stability and alignment in the cervical region, as well as McKenzie neck exercises, which focus on correcting neck posture.This study aims to determine the effect of scapular stabilization exercises and McKenzie neck exercises on increasing the craniovertebral angle in adolescents aged 13–15 years with forward head posture at SMP Muhammadiyah 16 Lubuk Pakam in 2025. The study employed a quasi-experimental design using a one-group pre-test and post-test approach. The interventions were administered twice a week for four weeks, with a total of eight sessions. Measurements were conducted using a goniometer. The results showed that the mean craniovertebral angle before the intervention was 45.00 with a standard deviation of 1.414, and after the intervention, it increased to 47.43 with a standard deviation of 1.604. Data analysis using the paired sample t-test revealed a p-value of 0.000, which is smaller than α = 0.05, indicating a significant difference between pre- and post-intervention measurements. Therefore, it can be concluded that scapular stabilization exercises and McKenzie neck exercises have an effect on improving the craniovertebral angle in adolescents aged 13–15 years with forward head posture at SMP Muhammadiyah 16 Lubuk Pakam in 2025